The Impact of Lamina Characteristics and Types on Organic Matter Enrichment of Chang 73 Submember in Ordos Basin, NW China. (18th June 2022) - Bian, Congsheng; Zhao, Wenzhi; Yang, Tao; Liu, Wei; Dai, Chaocheng; Zeng, Xu; Wang, Kun; Li, Yongxin; Xiao, Di
Abstract : The Chang 7 member in Ordos Basin is an important shale oil exploration layer, with new shale-oil discoveries in recent years. The Chang 73 submember is rich in organic shale, which is the main source rock of shale oil in the Yanchang Formation. In order to clarify the lamina structure, composition, types, and distribution characteristics in Chang 73 submember and its influence on organic matter enrichment, a full coring well in Chang 73 submember located in deep-lacustrine facies is selected to obtain intensive systematic core samples. Core observation, thin section identification, X-ray fluorescence element analysis, X-diffraction analysis, scanning electron microscope, electron probe, rock pyrolysis, and other techniques are performed to systematically analyze the morphology, structure, thickness, mineral compositions, and organic matter content of the shale lamina in the Chang 73 submember. Five types of lamina are identified: silty felsic lamina (SF), tuffaceous lamina (TF), organic-rich clay lamina (ORC), organic-bearing clay lamina (OBC), and homogeneous clay lamina (HC), which are further subdivided into eight subtypes. The lamina types change greatly vertically in the Chang 73 submember, in which the lower part is mainly silty felsic lamina, organic-rich clay, and tuffaceous lamina, the middle part is mainly organic rich and organic clay lamina and organic-bearing clay lamina, and the upper part is mainly homogeneous clay lamina and a small amount of silty felsic organic-bearing clay lamina and organic-bearing clay lamina. Different laminae show various organic matter types, organic matter content (TOC), and organic matter occurrence states which can be divided into four occurrence types. The TOC in organic-rich clay lamina and part of homogeneous clay lamina is high, while that of silty felsic lamina is lower. The relationship between shale lamina and organic matter enrichment is established according to the correlation analysis of laminar characteristics, mineral content, and organic matter content. Among them, the organic-rich lamina is richest of TOC and is a favorable "sweet point" for shale oil exploration.